Kaempferol, quercetin và dẫn xuất diglycosid của chúng tách từ lá chay bắc bộ (Artocarpus tonkinensis) - Thủy, Trịnh Thị; Thiện, Đào Đức; Tâm, Nguyễn Thanh; Kim Dung, Lại Thị; Sung, Trần Văn; Delfino, Domenico V. (Vietnam Journal of Chemistry, 2016)
The present study reported the isolation and identification of five flavonols named kaempferol, kaempferol 3-rutinoside, kaempferol 3-neohesperidoside, quercetin-3-O-b-D-glucopyranoside and quercetin 3-rutinoside from the leaves of Artocarpus tonkinensis A. Chev. ex Gagnep. Their structures were identified by combination of spectroscopic methods (NMR, HR-ESI-MS) and comparison with reported data. Three flavonol glycosides kaempferol 3-rutinoside, kaempferol 3-neohesperidoside and quercetin 3-rutinoside were found for the first time in the genus Artocarpus J.R. Forst. & G. Forst. Keywords. Artocarpus tonkinensis; astragalin; kaempferol 3-rutinoside; kaempferol 3-neohesperidoside; quercetin 3-rutinoside.